Comparing social media use in school management: experiences from Ukraine and the United States - Liubov A. Kartashova; Nataliia O. Prykhodkina; Tetiana A. Makhynia; Hanna M. Tymoshko; Olena A. Sholokh (Academy of Cognitive and Natural Sciences, 2024)
This paper analyses and compares the use of social media in school management in Ukraine and the United States. It examines the types of social media used, purposes for use, and challenges faced. Key findings show that Facebook, YouTube, Instagram and X are most popular in both countries. Social media communicates with stakeholders, showcases school activities, and builds relationships. Challenges include data privacy, digital literacy, and misinformation. The paper reviews training programs in both countries to improve social media competency for school leaders. It concludes that social media has become an essential communications tool in education, accelerated by the pandemic's impacts.